2017
DOI: 10.1037/ocp0000072
|View full text |Cite
|
Sign up to set email alerts
|

Safety climate and culture: Integrating psychological and systems perspectives.

Abstract: Safety climate research has reached a mature stage of development, with a number of meta-analyses demonstrating the link between safety climate and safety outcomes. More recently, there has been interest from systems theorists in integrating the concept of safety culture and to a lesser extent, safety climate into systems-based models of organizational safety. Such models represent a theoretical and practical development of the safety climate concept by positioning climate as part of a dynamic work system in w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
65
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(76 citation statements)
references
References 86 publications
2
65
0
2
Order By: Relevance
“…Relevant syntheses of studies concerning the effect of safety climates have been reported in reviews and meta-analyses (e.g. Beus, McCord, & Zohar, 2016;Burke & Signal, 2010;Casey, Griffin, Flatau Harrison, & Neal, 2017;Christian et al, 2009;Clarke, 2006Clarke, , 2010Cornelissen, Van Hoof, & De Jong, 2017;Glendon, 2008;Griffin & Curcuruto, 2016;Guldenmund, 2000;Jiang et al, 2019;Nahrgang, Morgeson, & Hofmann, 2011;Schonfeld & Chang, 2017). Nevertheless, those meta-analytic studies and reviews reveal that many issues remain unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…Relevant syntheses of studies concerning the effect of safety climates have been reported in reviews and meta-analyses (e.g. Beus, McCord, & Zohar, 2016;Burke & Signal, 2010;Casey, Griffin, Flatau Harrison, & Neal, 2017;Christian et al, 2009;Clarke, 2006Clarke, , 2010Cornelissen, Van Hoof, & De Jong, 2017;Glendon, 2008;Griffin & Curcuruto, 2016;Guldenmund, 2000;Jiang et al, 2019;Nahrgang, Morgeson, & Hofmann, 2011;Schonfeld & Chang, 2017). Nevertheless, those meta-analytic studies and reviews reveal that many issues remain unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…However, there was little detail on employee involvement in the development of a company's strategy and there was a clear inference that a good food safety strategy is aimed at avoiding prosecution and jeopardising key accounts rather than energising the company culture with its associated benefits, such as enhanced morale, reduced non-compliance and the generation of innovative solutions as supported by Casey., et al [33]. This is indicated by the statement below:…”
Section: Theme 1: Controlmentioning
confidence: 97%
“…Furthermore, there equally appears to be additional mixed perceptions that an organisation's 'safety climate' addresses issues associated with employee attitudes towards safety. Whilst safety culture is occupied with employees' prevailing values within the organisation management need to recognise that the so-called three labels, namely safety culture, food safety culture and safety climate, collectively establish an organisation's holistic culture [33]. To treat them as separate entities is folly, as one need only refer to the media in repeatedly covering food safety accidents and incidents.…”
Section: Systems (Fsms) Such As Iso 22000 Hazard Analysis and Criticalmentioning
confidence: 99%
See 1 more Smart Citation
“…The safety climate is of particular interest, as it involves some of the informal aspects of a work community and may provide a glimpse into the safety culture [19]. In this research, safety climate is defined as the shared perceptions regarding safety policies, procedures and practices, and regarding how safety is managed and valued [20,21,22]. Empirically, the study is based on a quantitative questionnaire study, involving 428 sharp end workers in the Norwegian fish farming industry.…”
Section: Objectives and Hypothesesmentioning
confidence: 99%